A synthetic cohort analysis of postoperative management of primary cardiac angiosarcoma and a case report - Cai, Ying; Yang, Hang; Yuan, Dan; Jin, Su-Han; Xu, Junzhu; Hu, Wei; Bai, Yuju; Li, Xinjuan; Wang, Zejin; Zhang, Dengshen; Guo, Ke; Wang, Shixiang; et al. (Frontiers in Oncology, 2025)
BackgroundPrimary cardiac angiosarcoma is a rare and aggressive malignancy originating from the endothelial lining of cardiac blood vessels. The prognosis remains extremely poor. The study was to evaluate postoperative survival in patients with primary cardiac angiosarcoma after treated with adjuvant therapy.MethodsA systematic review of PubMed from January 1985 to December 2023 was performed to establish a synthetic cohort of patients undergoing surgery for primary cardiac angiosarcoma. Survival analysis was used to assess the relationship between postoperative adjuvant therapy and prognosis. Univariable and multivariable cox regression analyses were used to identify prognostic factors. We then established and validated a nomogram by receiver operating characteristic (ROC) curves, calibration curves and decision curve analysis (DCA). Moreover, we present a case of 49-year-old patient with primary cardiac angiosarcoma.ResultsIn the synthetic cohort, the patients with postoperative adjuvant therapy reached longer overall survival (OS) and progression-free survival (PFS) than those without postoperative adjuvant therapy (median OS: 14 VS 8 months, HR = 5.62, 95%CI: 1.66-19.08, P<0.001; median PFS: 12 VS 6 months, HR = 2.98, 95%CI: 1.03-8.66, P = 0.007; Log rank test). Radiotherapy (HR = 0.14, 95% CI: 0.04-0.54, P = 0.004) and chemotherapy (HR = 0.03, 95% CI: 0.00-0.27, P = 0.002) were significantly correlated with better OS. DCA and ROC curves confirmed the nomogram can predict postoperative 6-month survival in patients with primary cardiac angiosarcoma. OS was indistinguishable between patients with R0 or R1 resection (10 VS 10 months, HR = 0.99; 95%CI: 0.34-2.86; P = 0.986). However, compared to patients underwent R1 resection, patients undergoing R0 resection have longer but not statistically significant PFS (10 VS 7 months, HR = 2.16; 95%CI: 0.83-5.61; P = 0.090).ConclusionThe prognosis of patients with primary cardiac angiosarcoma remains extremely poor, even with surgical resection. Postoperative adjuvant therapy was associated with significantly better survival in a small cohort of patients with primary cardiac angiosarcoma. Further studies are warranted to guide future recommendations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251139779.